Attracting Interest in Buying Queen Petshop Stores With Social Media Data - Ibrahim, Muhammad Arya; Wibowo, Sampurno (Yayasan Riset dan Pengembangan Intelektual, 2024)
The pet shop business in Indonesia is presently undergoing substantial expansion. Based to the Indonesian Pet Food Association (AMHKI), the pet food industry in Indonesia is expected to experience a yearly growth rate of 20%. The majority of the market, accounting for 60%, is centered in Java, which includes Jakarta and other large cities. Intelligent web scrapers have uncovered data indicating that there are a total of 296 pet businesses located exclusively in Jakarta. Consequently, businesses are required to maintain competitiveness and allure clients via social media. Queen Petshop, a pet shop enterprise, using Instagram as a platform to disseminate information regarding their merchandise to their target audience. Nevertheless, Queen Petshop has had difficulties in producing captivating material. The objective of this study is to leverage Instagram social media data in order to create content for Queen Petshop's Instagram account (@queenpetshop) that will generate interest in making purchases. The study utilizes a qualitative methodology with a descriptive orientation. Data were gathered by the methods of observation, interviews, and documentation. The results suggest that utilizing social media data strategically to generate content will greatly boost the purchase intent for Queen Petshop.